A indeterminação pragmática e semântica do sujeito - Teixeira, Maria Luiza de Sousa [UNESP] (2014)
The indeterminacy of the syntactic function subject has been defined, generally, as a semantic concept involving the notion of lack of reference. In this study, however, we aimed to demonstrate that indeterminacy is a remarkably pragmatic process of different forms of morphosyntactic coding. Based on the theoretical approach of the Functional Discourse Grammar (HENGEVELD; MACKENZIE, 2008), the reference is assumed as a pragmatic concept that is intrinsically related to the fact that the speaker is able to, is willing or is not willing to, identify a referent. Thus, the referent is built into the interaction through discursive and cognitive practices which are socially and culturally situated. Thus, it is in the speech that the speaker expresses the indeterminacy. In order to formulate a concept of indeterminacy that focuses on its pragmatic, semantic and syntactic complexity, the description of the grammatical coding of indeterminacy is based on a sample of different textual genres of argumentative basis of written Brazilian Portuguese. Besides the description of a very diverse forms of indeterminacy strategies, the results showed different types of indeterminacy, as defined only to the speaker, to the listener only, or to both, which led us to propose three types of subject indeterminacy. The integrated analysis of pragmatic, semantic and morphosyntactic levels enabled by the theoretical approach of FDG also allowed the clarification of the relationship between indeterminacy and vagueness. Although this proposal has no intended didactic goals, some possible applications of this research for teaching purposes are discussed